DIAGNOSTIC AND TREATMENT IN TETANY: EXPLORING NON-HYPOCALCEMIC CAUSES AND CLINICAL CHALLENGES - Zofia Laska; Marianna Latour; Zuzanna Kudlińska; Honorata Juniewicz; Patryk Heryć; Karolina Kananowicz; Ryszard Łagowski; Julia Kosęda; Anna Jędrasiak; Jakub Piotrowski (International Journal of Innovative Technologies in Social Science, 2025)
Normocalcemic tetany is a clinical condition characterized by neuromuscular hyperexcitability in the absence of overt hypocalcemia, resulting from disturbances in ionized calcium, magnesium, potassium, or acid–base balance. Although tetany is most commonly associated with hypocalcemia, cases with normal total calcium levels pose diagnostic challenges and are frequently underrecognized. This review consolidates current knowledge regarding the etiology, clinical manifestations, diagnostic evaluation, and management of normocalcemic tetany. The etiology includes hereditary renal tubulopathies such as Gitelman and Bartter syndromes, hyperventilation-related alkalosis, magnesium deficiency, and rare autoimmune disorders involving antibodies against the voltage-gated potassium channel complex (CASPR2). Clinical presentations range from overt tetanic seizures with characteristic carpopedal spasms to latent tetany detectable via Chvostek and Trousseau signs or ischemia-induced EMG abnormalities. Case reports highlight unusual scenarios, including tetany triggered by vomiting, postoperative parathyroidectomy, and hereditary neuromuscular hypersensitivity, emphasizing that serum total calcium may remain normal while ionized calcium or other electrolytes fluctuate. Management strategies focus on prompt recognition, correction of underlying electrolyte disturbances—particularly calcium, magnesium, and potassium—and supportive care. Early administration of intravenous calcium, alongside addressing precipitating factors, is critical for rapid symptom relief. Latent or recurrent tetany in the context of normal electrolytes warrants consideration of genetic, neurologic, or autoimmune etiologies, and may require specialized testing including EMG, antibody panels, or genetic analysis. Increased awareness among clinicians, timely evaluation of ionized calcium and other electrolytes, and early intervention are essential to prevent severe complications, including life-threatening muscle spasms, rhabdomyolysis, and cardiovascular instability. This review underscores the need for further population-based studies to define the prevalence, at-risk groups, and optimal management of normocalcemic tetany.